Chewing and swallowing as key functions for a good start to complementary feeding in children: Literature Review - Yupanqui-Barrios1, Kasandra V. (2024)
Objective: To provide relevant information related to chewing and swallowing as key elements for the prevention of children eating difficulties. Literature Review: It is known that digestion begins in oral cavity, thus, it can be established that the processes of chewing and swallowing are typical of the feeding processes that are initially built in the family, managed through guidance and/or consultations in the field of pediatric dentistry and other related areas.. The role of the pediatric dentist is to guarantee adequate guidance that allows families to recognize possible alerts that could interfere with a good start to complementary feeding in babies and young children. Some eating difficulties are usually related to a lack of competence in swallowing and chewing functions. This may be due to poor neuromuscular stability, comfort, connection with the feeding processes, as well as environmental conditions and the challenges of eating. the nourishment they generate from the need to reflect and promote a more interdisciplinary view. Conclusion: Chewing and swallowing are part of the prevention and detection of eating difficulties, therefore, pediatric dentists should train and work in an interdisciplinary manner with the phonoaudiologist to diagnose and plan treatments comprehensively.